A case report: Twin sisters with restrictive cardiomyopathy associated with rare mutations in the cardiac troponin I gene. Issue 4 (April 2021) - Ueno, Michihiko; Takeda, Atsuhito; Yamazawa, Hirokuni; Takei, Kohta; Furukawa, Takuo; Suzuki, Yasuto; Chida-Nagai, Ayako; Kimura, Akinori
Abstract: Restrictive cardiomyopathy (RCM) is a rare cardiomyopathy in children, and its prognosis until now, has been poor. Recently some sarcomeric mutations have been reported as disease-causing genes of RCM. However, the genotype-phenotype correlation is not fully understood. Additionally, prognostic factors including sudden death in patients with RCM have not been elucidated. We report our experience in treating twin sisters with RCM or hypertrophic cardiomyopathy with RCM phenotype, both carriers of the same mutation in TNNI3, which encodes one of the major sarcomeric proteins in myofibrils. They were both diagnosed with RCM by cardiac catheterization at the age of 11 years. Despite appropriate follow-up and medical treatment, one died suddenly at the age of 11 years and the other also died at the age of 15 years due to heart failure while awaiting heart transplantation. In addition to our cases, other reports of younger fatal cases with RCM carrying TNNI3 mutations may suggest it as one of the prognostic factors. Genetic diagnosis is important in the clinical diagnosis, management, and treatment of cardiomyopathy. <Learning objective : Our cases involved twin sisters diagnosed with restrictive cardiomyopathy (RCM) with rare mutations in the cardiac troponin I. Based on their clinical course, this mutation appears to have a poor prognosis. It was reported that RCM was caused by sarcomere gene mutations, however, the relationship between genotype and phenotype is not clearly defined. To elucidate the prognosis of this rare disease not only the genetic mutations but the accumulation of various clinical outcomes is important.>